The CBM Time-of-Flight system - Deppner, Ingo Martin; Herrmann, Norbert (Journal of Instrumentation, 2019)
The Compressed Baryonic Matter spectrometer (CBM) is a future fixed-target heavy-ion experiment located at the Facility for Anti-proton and Ion Research (FAIR) in Darmstadt, Germany. The key element in CBM providing hadron identification at incident beam energies between 2 and 11 AGeV (for Au-nuclei) will be a 120 m2 large Time-of-Flight (ToF) wall composed of Multi-gap Resistive Plate Chambers (MRPC) with a time resolution of the system better than 80 ps. Aiming for an interaction rate of 10 MHz for Au+Au collisions the MRPCs have to cope with an incident particle flux between 0.1 kHz/cm2 and 100 kHz/cm2 depending on their location. Being the system characterized by wide ranges of both granularity and rate capability, the conceptual design of the ToF-wall foresees 6 different granularities and 4 different detector designs. In order to elaborate the final MRPC design of these counters several heavy-ion in-beam and cosmic-ray tests were performed. In this contribution we present the conceptual design of the TOF wall and discuss the performance results of full-size MRPC prototypes.